Role of estrogen in renal handling of organic cation, tetraethylammonium: In vivo and in vitro studies - Paranee Meetam (2018)
This study examined the effect of estrogen (17β-estradiol) on renal handling of organic cation, tetraethylammonium (TEA), both in vivo and in vitro. Clearance of TEA in ovariectomized (OVX) mice was increased by 38% above intact animals, which was able to be returned to control level by estrogen supplementation. The mechanism of this effect was examined in isolated mouse renal proximal tubules (mRPT), showing that [3H]-TEA uptake was higher in OVX mice than control, and estrogen supplementation returned uptake to normal level. Kinetics analysis of [3H]-TEA uptake indicated an increase in numbers of organic cation transporters in OVX mice but no change in substrate affinity. However, mRNA levels determined by quantitative real time polymerase chain reaction of the relevant transporters at basolateral (organic cation transporter (OCT)1, OCT2 and OCT3) and apical (organic cation/carnitine transporter (OCTN)1, OCTN2 and multidrug and toxin extrusion (MATE)1) membranes of OVX mice were not significantly changed, with only MATE2 mRNA of OVX mice being significantly decreased. The realization that estrogen status affects renal clearance of organic cations will be of importance when assessing the susceptibility of an individual to drug-induced toxicity. © 2009 Pharmaceutical Society of Japan.